Efeito da desidratação osmótica na germinação de sementes de vinte cultivares de feijão (Phaseolus vulgaris L) - Machado , Regina C R; Braga Rena, Alemar; Vieira , Clibas (Revista Ceres, 2025)
The germination and the initial growth of the seedlings of 20 bean (Phaseolus vulgaris L.) cultivars have been examined under various levels of osmotic desiccation. The germination and the growth of the seedlings were both highly affected by solutions of NaCl and manitol of various water potentials, and there were differences among the cultivars in relation to both processes. At the lowest water potentials the germination was more affected in NaCl than in manitol, and this difference was probably caused by the osmotic and toxic effects of the sodium chloride solutions. Therefore, manitol seems to be an osmotic agent more effective than the NaCl to induce water deficit during germination. There is a significant positive correlation between the weight of the seeds and the percent